2020
DOI: 10.1016/j.ejpb.2020.02.005
|View full text |Cite
|
Sign up to set email alerts
|

An interlaboratory investigation of intrinsic dissolution rate determination using surface dissolution

Abstract: The purpose of this study was to conduct an interlaboratory ring-study, with six partners (academic and industrial), investigating the measurement of intrinsic dissolution rate (IDR) using surface dissolution imaging (SDI) equipment. Measurement of IDR is important in pharmaceutical research as it provides characterising information on drugs and their formulations. This work allowed us to assess the SDI's interlaboratory performance for measuring IDR using a defined standard operating procedure (see supporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…The apparent larger variation in the PAR IDR determination is largely skewed by the inflated IDR determination for the 0.25 kN experiments. Similar levels of variation have been reported using the Sirius SDI dissolution imaging system, a predecessor of the instrument applied in the current study (10), and the μDISS Profiler™ (9). Etherson et al reported in an inter-laboratory small-scale dissolution study that the relative standard deviation (expressed as a percentage) of IDR values varied from 33-130 % using 6 compounds (n = 6), and FaSSIF and blank FaSSIF as the dissolution media across seven sites (10).…”
Section: Intrinsic Dissolution Rate Determinationssupporting
confidence: 80%
See 2 more Smart Citations
“…The apparent larger variation in the PAR IDR determination is largely skewed by the inflated IDR determination for the 0.25 kN experiments. Similar levels of variation have been reported using the Sirius SDI dissolution imaging system, a predecessor of the instrument applied in the current study (10), and the μDISS Profiler™ (9). Etherson et al reported in an inter-laboratory small-scale dissolution study that the relative standard deviation (expressed as a percentage) of IDR values varied from 33-130 % using 6 compounds (n = 6), and FaSSIF and blank FaSSIF as the dissolution media across seven sites (10).…”
Section: Intrinsic Dissolution Rate Determinationssupporting
confidence: 80%
“…Similar levels of variation have been reported using the Sirius SDI dissolution imaging system, a predecessor of the instrument applied in the current study (10), and the μDISS Profiler™ (9). Etherson et al reported in an inter-laboratory small-scale dissolution study that the relative standard deviation (expressed as a percentage) of IDR values varied from 33-130 % using 6 compounds (n = 6), and FaSSIF and blank FaSSIF as the dissolution media across seven sites (10). For IBU, there was a large variation in the absolute measured IDR values from the two generation of the SDI equipment.…”
Section: Intrinsic Dissolution Rate Determinationssupporting
confidence: 80%
See 1 more Smart Citation
“…Intrinsic dissolution rate (IDR) is defined as the rate of mass transfer per a unit area which is exposed to dissolution media (130). Throughout an experiment, the IDR surface area should be kept constant, and the use of a constant flow of dissolution media (in the case of UV dissolution imaging) applied to maintain sink conditions.…”
Section: Small-scale Dissolution and Intrinsic Dissolution Rate Measu...mentioning
confidence: 99%
“…Hydrogel matrixes have been used together with UV imaging to determine drug diffusion [ 19 ] and drug release from different vehicles into hydrogels [ 11 , 20 , 21 ]. UV imaging has been used to characterize dissolution behavior, including determination of intrinsic dissolution rates for active pharmaceutical ingredients [ 22 , 23 ]. UV imaging has also found use in characterizing the performance of injectable formulations [ 15 , 18 ].…”
Section: Introductionmentioning
confidence: 99%